From TshwaneLex to TshwaneTerm: Tailoring Terminology Management for South Africa - Joffe, David; De Schryver, Gilles-Maurice (Lexikos, 2005)
ABSTRACT: The addition of a restricted number of features to the dictionary (compilation) soft-ware TshwaneLex suffices to turn this application into a terminology management system. This article gives a brief overview of those extra features, using the Department of Arts and Culture (DAC) AIDS list as case study. Keywords: LEXICOGRAPHY, TERMINOLOGY LIST, TERMINOLOGY MANAGEMENT SYSTEM, SOFTWARE, TSHWANELEX, TSHWANETERM, DAC AIDS LIST ***** SAMEVATTING: Van TshwaneLex naar TshwaneTerm: terminologiebeheer op maat voor Zuid-Afrika. De toevoeging van een beperkt aantal uitbreidingen aan de woor-denboek(aanmaak)software TshwaneLex is voldoende om dit programma met succes als terminolo-giebeheersysteem in te zetten. Dit artikel geeft een kort overzicht van die extra uitbreidingen, en gebruikt de Department of Arts and Culture (DAC) AIDS lijst als illustratie. Sleutelwoorden: LEXICOGRAFIE, TERMINOLOGIELIJST, TERMINOLOGIEBEHEER-SYSTEEM, SOFTWARE, TSHWANELEX, TSHWANETERM, DAC AIDS LIJST